Synthesis and properties of novel star-shaped oligofluorene conjugated systems with BODIPY cores - Orofino-Pena, Clara; Cortizo-Lacalle, Diego; Cameron, Joseph; Sajjad, Muhammad T.; Manousiadis, Pavlos P.; Findlay, Neil J.; Kanibolotsky, Alexander L.; Amarasinghe, Dimali; Skabara, Peter J.; Tuttle, Tell; Turnbull, Graham A.; Samuel, Ifor D. W. (Beilstein Journal of Organic Chemistry, 2014)
Star-shaped conjugated systems with varying oligofluorene arm length and substitution patterns of the central BODIPY core have been synthesised, leading to two families of compounds, T-B1–T-B4 and Y-B1–Y-B4, with T- and Y-shaped motifs, respectively. Thermal stability, cyclic voltammetry, absorption and photoluminescence spectroscopy of each member of these two families were studied in order to determine their suitability as emissive materials in photonic applications.
Keywords: absorption spectroscopy; BODIPY; cyclic voltammetry; photoluminescence; star-shaped oligofluorene